Urethrovaginal fistula: is fistuloplasty always indicated? - R. A. Shakhaliev; N. D. Kubin; A. S. Shulgin; F. K. Sintsov; D. D. Shkarupa (Вестник урологии, 2025)
Introduction. A urethrovaginal fistula is a type of genitourinary fistula characterised by an abnormal communication between the urethra and the vagina. The principal clinical features include urinary leakage through the vagina, partial or complete stress urinary incontinence (SUI) precipitated by coughing, sneezing, or physical exertion, as well as dysuria and spraying of the urinary stream.Objective. We present a clinical case demonstrating the possibility of addressing the patient’s primary complaint through the placement of an adjustable suburethral sling (SUS) without closure of the urethral fistula.Case presentation. A 44-year-old female patient was diagnosed with SUI, urethrovaginal fistula, and meatal obliteration. At the time of examination, she reported significant urinary leakage during coughing, sneezing, and physical exertion, altered urinary stream direction, and urine leakage from the vagina following micturition. The symptoms first appeared in 2005 postpartum, complicated by urethral prolapse with subsequent excision of the necrotic distal segment. On examination, the external urethral meatus was obliterated. A fistulous opening was observed 15 mm proximal to the obliterated urethral meatus. The urethral length measured 25 mm. The cough stress test was positive. Quality of life questionnaire scores were as follows: POPDI-6 — 8.33, CRADI-8 — 25, UDI-6 — 50, PFDI-20 — 83.33; PISQ-12 — 23; ICIQ-SF — 10. The patient underwent implantation of an adjustable SUS. Postoperatively, sling tension was adjusted. At 12-month follow-up, the cough stress test was negative. Voiding was unobstructed with no residual urine. A significant improvement in quality of life was noted according to questionnaire scores: POPDI-6 — 5, CRADI-8 — 0, UDI-6 — 4, PISQ-12 — 38, ICIQ-SF — 2.Conclusion. This clinical case demonstrates the successful use of an adjustable SUS to address the primary complaint of SUI in a patient with a urethrovaginal fistula.